Does Multidimensionality Cause DIF? - Ali Ridho (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2018)
The differential item functioning (DIF) of an item that initially assumed unidimensional is frequently attributed to the assumption of multidimensionality. Therefore, it is important to test the assumption that multidimensionality causes an item to be functionally different between the disadvantaged group (i.e. focal group) and the benefited group (i.e. reference group) on the Aptitude Potential Test for New Student Selection in State Islamic University (AP SPMB-PTAIN). This study aims to: (a) explore and confirm the internal structure of AP SPMB-PTAIN; (b) identify items containing DIF based on the types of school the candidates attended (Madrasah Aliyah/MA, that is, secondary education managed by the Ministry of Religious Affairs, or regular high school/SMA); and (c) evaluate the multidimensionality effects on DIF. The data analyses (n = 10,000) showed that: (1) the internal structure of AP SPMB-PTAIN is semi-complex multidimensional; (2) 15 items contain DIF UIRT (12 items benefited high school graduates while three items benefited MA graduates); five items contain DIF MRT that benefited high school graduates; and (3) the multidimensionality difference between the focal and reference group did not appear to correspond to DIF.